Association of Bolster Duration With Uptake Rates of Fibula Donor Site Skin Grafts. - David, Abel P.; Heaton, Chase; Park, Andrea; Seth, Rahul; Knott, P. Daniel; Markey, Jeffrey D. (JAMA Otolaryngology-Head & Neck Surgery, 2020)
Importance: The fibula free flap donor site is associated with both short-term and long-term morbidity. Split-thickness skin graft (STSG) loss can lead to long delays in donor site healing and is associated with significant adverse sequelae. Patients may experience initial good STSG uptake after bolster removal but may have subsequent partial or total loss related to contact pressure or shearing.Objective: To determine if increased duration of bolster use is associated with increased STSG uptake rates following fibula free flap reconstruction.Design, Setting, and Participants: This retrospective cohort study included patients 18 years and older undergoing fibula free flap reconstruction following head and neck extirpative surgery at a tertiary care academic medical center from May 2013 to March 2019. The donor sites were photographed 4 weeks postoperatively, and areas of graft uptake were measured using image processing software. The baseline demographic, comorbidity, and operative characteristics were also collected.Interventions: A fine mesh gauze with 3% bismuth tribromophenate and petrolatum blend bolster was sutured over leg STSGs placed on fibula free flap donor sites intraoperatively, and the ankle and lower leg were immobilized for 5 days in a plaster splint. Bolsters were either removed on postoperative day 5 or 14. Thereafter, the STSGs were covered with a petroleum and bismuth gauze and a cotton dressing.Main Outcomes and Measures: Rates of donor site infection and STSG percentage uptake at 4 weeks.Results: Of the 42 included patients, 31 (74%) were male, and the mean (SD) age was 62.1 (13.1) years. A total of 20 patients were included in the 5-day group, and 22 were included in the 14-day group. The 14-day bolster group had a higher mean percentage skin graft uptake rate compared with the 5-day bolster duration group (77.5% vs 59.9%), with an effect size of -0.632 (95% CI, -1.260 to -0.004). Patients with Adult Comorbidity Evalution-27 scores of 3 had poorer rates of STSG uptake compared with patients with Adult Comorbidity Evalution-27 scores of 0 to 2 (65.9% vs 82.9%), with an effect size of 0.599 (95% CI, -0.191 to 1.389). No donor site infections were noted in either group.Conclusions and Relevance: Fourteen-day bolster application to the fibula free flap donor site was associated with better STSG uptake rates than 5-day bolster application.